CENTRAL ASIA: SCO AND NATO IN REGIONAL AND GLOBAL POLITICS - PLASTUN, Vladimir (CENTRAL ASIA AND THE CAUCASUS, 2008)
There is a more or less general agreement among political scientists that the center of gravity of the most important (or even critically important) world developments is shifting toward Central Asia. The sequence of events brings us back to square one: the Soviet Union’s disintegration and the emergence of the newly independent states. A potential boon that could have opened access to the region’s oil and gas riches and could have enriched the local states and their extra regional partners was buried by the inadequate behavior of the sides involved. Business cooperation presupposes mutual understanding and mutual concessions for the sake of mutual benefit. It would have been wise to keep political and ideological considerations and business strictly apart, but this is much harder to achieve in reality. Reality proved different: encouraged by the disintegration of the Soviet “empire of evil,” the West, led by the United States, tried to use this opportunity to achieve unilateral advantages. An article by Helena Cobban, member of the Friends Committee on National Legislation, which appeared in Christian Science Monitor reminded everyone that the interests of the world powers were closely intertwined. Indeed, China and Japan are the largest among America’s creditors while Russia is one of Europe’s largest suppliers of energy resources. Market, investment, and production structures are intertwined and know no state borders.1 We might have rejoiced at these developments which could have improved, in the near future, the living standards of the destitute population groups across the planet, extinguished the national, religious, and ethnic conflicts, and done away with the unipolar world as the political and economic hegemony of one state. But it is too early to talk about the end of the Cold War and laying the cornerstone of mutual understanding.